Redefining Hepatocellular Carcinoma Staging Systems Based on the Bile Duct Invasion Status: A Multicenter Study - Huang, Qizhen; Chen, Yufeng; Lin, Kongying; Sun, Chuandong; Zheng, Shuguo; Chen, Jinhong; Wang, Yifan; Zhou, Yanming; Zhou, Weiping; Liu, Jingfeng; Zeng, Yongyi (Frontiers in Oncology, 2021)
Background and Aims: The prognostic value of bile duct invasion (BDI) remains controversial. We aimed to investigate the prognostic value of BDI and the stage of BDI in different staging systems. Methods Patients with hepatocellular carcinoma (HCC) from nine hepatobiliary medical centers who underwent R0 resection were included. Overall survival (OS) was assessed using the Kaplan–Meier method and tested using the log-rank test. The prognostic effect of BDI was analyzed using univariate and multivariate Cox proportional hazard regression analyses. The predictive performance of these models was evaluated using the concordance index and time-dependent receiver operating characteristic curve (tdAUC). Results Of 1021 patients with HCC, 177 had BDI. OS was worse in the HCC with BDI group than in the HCC without BDI group (p<0.001); multivariate analysis identified BDI as an independent risk factor for OS. After adjustment for interference of confounding factors using the Cox proportional hazard regression model, HCC with BDI and without macrovascular invasion was classified as Barcelona Clinic Liver Cancer (BCLC) B, eighth edition American Joint Committee on Cancer (AJCC) IIIA, and China Liver Cancer (CNLC) IIb, respectively, whereas HCC with BDI and macrovascular was classified as BCLC C, AJCC IIIB, and CNLC IIIA, respectively. C-indexes and tdAUCs of the adjusted staging systems were superior to those of the corresponding current staging systems. Conclusion We constructed adjusted staging systems with the BDI status, improved their predictive performance and facilitate clinical use.